2019
DOI: 10.21533/pen.v7i1.373
|View full text |Cite
|
Sign up to set email alerts
|

Virtual mobility for students, going from distance learning to live participation

Abstract: Paper reviews differences between virtual mobility and distance learning, providing insight into current state of art for online learning in higher education. Authors analyze main barriers and obstacles for live virtual mobility to become a mainstream practice as well as justify the possible regions of operation. Summary is provided for the most visible pilot projects that have paved the way for the term virtual mobility to become an object of interest. Main impact factors are listed and the discussion part su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Taking a closer look at the possible set of criteria for VE activities, results show that the formal learning activities of students at their host institutions were digital or online, involved communication with peers from diverse international settings regularly or occasionally during the entire semester. These reflections are in line with the beforementioned criteria of VE (Erdei & Káplár-Kodácsy, 2020), being a digitally mediated intercultural learning experience for students from multiple institutional and national backgrounds that provided primarily synchronous learning during a medium-or long period of time (Andone et al, 2018;Bijnens et al, 2006;De Castro et al, 2019;Henderikx & Ubachs, 2019;Kayumova, 2016;Montes et al, 2011;Tereseviciene et al, 2015;Valtins & Muracova, 2019;Vriens et al, 2010).…”
Section: 'Emergency-mode' Virtual Exchange Programmessupporting
confidence: 70%
See 1 more Smart Citation
“…Taking a closer look at the possible set of criteria for VE activities, results show that the formal learning activities of students at their host institutions were digital or online, involved communication with peers from diverse international settings regularly or occasionally during the entire semester. These reflections are in line with the beforementioned criteria of VE (Erdei & Káplár-Kodácsy, 2020), being a digitally mediated intercultural learning experience for students from multiple institutional and national backgrounds that provided primarily synchronous learning during a medium-or long period of time (Andone et al, 2018;Bijnens et al, 2006;De Castro et al, 2019;Henderikx & Ubachs, 2019;Kayumova, 2016;Montes et al, 2011;Tereseviciene et al, 2015;Valtins & Muracova, 2019;Vriens et al, 2010).…”
Section: 'Emergency-mode' Virtual Exchange Programmessupporting
confidence: 70%
“…Merton's theory of educational functions (Merton, 1968) distinguishes between manifest or planned and latent or attained functions of education. In our study, we refer to Internet-connected ICT tools that are readily accessible and low cost to participating students (Andone et al, 2018;Bijnens, Boussemaere, Rajagopal, Beeck, & Van Petegem, 2006;De Castro, Dyba, Cortez, & PeBenito, 2019;Kayumova, 2016;Montes et al, 2011;Valtins & Muracova, 2019;Vriens, Van Variety of international educational formats or pedagogies (Henderikx & Ubachs, 2019) 11 Close collaboration and mutually confident relationship between international faculty and students (Montes et al, 2011) 12 Strategic use of a wide range of learning tools and technologies of the participating HEIs (Kayumova, 2016) 13 Student evaluation and grading by the own in-country faculty, which allows for learning objectives to be distinct between student groups (De Castro et al, 2019) 14 Joint choice of the subject to be offered through VE (Montes et al, 2011) 15 Joint learning resources (Montes et al, 2011) 16 Joint planning and selection of communication tools adequate for the planned T&L activities (Ma cek & Ritonija, 2016) 17…”
Section: Educational Functions and Structural Functionalismmentioning
confidence: 99%
“…Its concept has been evolved and developed well from the physical student mobility which has been applied in European Higher Education Institutions (HEI) for over 3 decades. Valtins and Muracova noted that Erasmus Program started in 1987 [1] becomes a prominent step in building the foundation of the virtual mobility concept. Erasmus is a program of student, professor and researcher exchange within European countries that provides participants' international experience, language training, new knowledge [1], intercultural competence [2] and networking.…”
Section: Introductionmentioning
confidence: 99%
“…Valtins and Muracova noted that Erasmus Program started in 1987 [1] becomes a prominent step in building the foundation of the virtual mobility concept. Erasmus is a program of student, professor and researcher exchange within European countries that provides participants' international experience, language training, new knowledge [1], intercultural competence [2] and networking. The main goal IOC is to increase the internationalization of European HEIs which will proportionally increase the academic quality of HEI themselves [2].…”
Section: Introductionmentioning
confidence: 99%
“…The interactive nature of Adobe Connect ® may have contributed to their satisfaction. Valtins and Muracova (2019) reported that Adobe Connect ® has good functionality as it allows the moderator to control participants' sound settings and the raising hand tool to ask a question and was the most preferred of the online platforms they evaluated. Similarly, Caliskan and others (2020) stated the educators in their study had positive experiences using Adobe Connect ® as an online education platform because it allows for active interaction, and its features provide an adequate level of support service (Caliskan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%